Multi-input Power Converter for Renewable Energy System with Droop Current Sharing Technique - Kamal, Khairunnisha (2018)
This paper proposed the design and simulation of a multi-input (3inputs) paralleled DC-DC Boost Converter with single output. By paralleling modules of power converter, it offers a lot of advantages over a single, centralized and high power supply converter but the drawback is, if one of the inputs is different compared to another two inputs, the output voltage will be affected. In order to overcome this problem and to achieve current sharing among those paralleled power converters, droop current sharing technique is being applied to this paralleled converters where in this technique, voltage droop via output current feedback schemes has been selected. In this scheme the error between the ouput voltage and the desired output voltage can be amplified using the PI and PID controller so that the controller can produce a new gate signal to regulate the desired output voltage which is 240V with 5% ripple. The author use 48V as the minimum voltage input for all paralleled converters and start to vary one or two of the inputs to see the change in the output voltage. The conventional multi-input paralleled converters did not manage to give a stable 240V as the input is vary but the multi-input paralleled converters with controller managed to give the desired output voltage which in line with the main objective to achieve current sharing among paralleled converters.